2010
DOI: 10.1016/j.ijid.2009.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Factors impacting compliance with standard precautions in nursing, China

Abstract: The relevant authorities and hospital infection control department should pay more attention to nurse compliance with standard precautions. Standard precautions training should be strengthened and sufficient practical personal protection equipment provided in order to reduce hospital infections and protect the health of patients and medical staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

31
184
8
45

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 171 publications
(268 citation statements)
references
References 10 publications
31
184
8
45
Order By: Relevance
“…Regarding the use of aprons, goggles and protective masks at times when there is possibility of blood spatter and secretions, the results were similar to those of other studies, which indicated a low adherence to using/wearing these PPE (2,4,16,20) . However, the use of disposable gloves was high, showing that this PPE is more embedded in the everyday routines of professionals.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Regarding the use of aprons, goggles and protective masks at times when there is possibility of blood spatter and secretions, the results were similar to those of other studies, which indicated a low adherence to using/wearing these PPE (2,4,16,20) . However, the use of disposable gloves was high, showing that this PPE is more embedded in the everyday routines of professionals.…”
Section: Discussionsupporting
confidence: 86%
“…In other international studies, low knowledge and professional adhesion to SP were also observed (15)(16)(25)(26)(27) , indicating that there are still differences in participation rates between developed countries and developing ones.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations